Entrepreneurial Attitudes and Interpersonal Communication in Teaching Students - Nafiati, Dewi Amaliah; Sukirno, Sukirno; Mulyani, Endang (Cakrawala: Jurnal Pendidikan, 2022)
The purpose of the study was to describe the entrepreneurial attitude and interpersonal communication of teaching students. This study uses a cross sectional design and a quantitative descriptive approach through the explanatory method. The research sample was 168 respondents with purposive sampling technique. The data collection technique used a questionnaire, the analysis technique was a technique for categorizing the mean results from hypothetical statistics and the Kruskal-Wallis test. The research findings are the entrepreneurial attitude of teacher students in the low category of 60.07% and the mean result of the Kruskall Wallis test is 31.7321. The students' interpersonal communication is also in the low category of 43.45% and the mean value of the Kruskall Wallis test is 26.6488. Practical and academic implications of research findings for policy makers and future researchers in the field of entrepreneurship education to find effective learning process formulations to shape entrepreneurial attitudes and improve teacher student interpersonal communication.